Climate data supports the adaptation of reindeer husbandry to climate change in Finland - Rasmus, Sirpa; Lehtonen, Ilari; Kumpula, Jouko; Landauer, Mia; Mettiäinen, Ilona; Sorvali, Jaana; Tuomenvirta, Heikki; Turunen, Minna
2022